Effect and Mechanism of Electroacupuncture at the Affected Side of Quchi （LI 11） and Yanglingquan （GB 34） Acupoints in Rats with Limb Spasms after Cerebral Infarction - ZHAN Sheng; HUANG Linxing; YI Lizhen; CHEN Ruixue; HUANG Huiyuan; YUE Zenghui (康复学报)
ObjectiveTo observe the effect of electroacupuncture at the affected side of Quchi (LI 11) and Yanglingquan (GB 34) acupoints on cortical injury and serum inflammatory factors [interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α)], glutamate (Glu), malondialdehyde (MDA), riboflavin kinase (RFK) and NADPH oxidase 2 (NOX2) in rats with post-stroke spasticity(PSS), and to investigate the mechanism of electroacupuncture in alleviating brain injury after ischemic stroke.MethodsA total of 30 SPF healthy adult male SD rats were randomly divided into sham operation group and model group, with 10 and 20 rats in each group. The PSS rat model was prepared by Zea-Longa suture method combined with internal capsule injection of N-methyl-D-aspartate (NMDA). After successful modeling, the model group was randomly divided into model group and electroacupuncture group, with 10 cases in each group. The rats in the model group were fixed with the rat plate without intervention, while those in the electroacupuncture group were subjected to electroacupuncture intervention. Yanglingquan (GB34, left) and Quchi (LI 11, left) acupoints on the affected side were selected, and each acupoint was directly punctured with one needle, dense wave pattern, the frequency at 100 Hz, and the intensity based on the slight shaking of rat limbs, 30 minutes a time, once a day, and the treatment lasted for 7 days. At the 1st day of modeling and the 7th day of the treatment, Zea-Longa neurological deficit score was used to assess the degree of neurological impairment. At the 2nd day of modeling and the 1st, 7th day of intervention, modified Ashworth scale (MAS) was used to assess muscle tension of the affected limbs. Hematoxylin-eosin (HE) staining was used to assess pathological changes of cerebral cortex. Enzyme-linked immunosorbent assay (ELISA) was used to detect the contents of MDA, Glu and IL-6, TNF-α in the cerebral cortex after the behavioral tests were completed. Western blot was used to analyze the protein expression level of RFK and NOX2. RT-PCR was used to analyze mRNA transcription levels of RFK and NOX2 mRNA.Results(1) Zea-Longa neurological deficit score and MAS score: compared with that before treatment, Zea-Longa neurological deficit score and MAS score of the electroacupuncture group decreased significantly after treatment (P<0.05). Compared with the sham operation group, Zea-Longa neurological deficit score and MAS score of the model group and the electroacupuncture group increased significantly after treatment (P<0.05). Compared with the model group, Zea-Longa neurological deficit score and MAS score of the electroacupuncture group decreased significantly after treatment (P<0.05). (2) Pathological changes of brain: some pathological changes(edema, hyperchromatic nuclei, irregular morphology, pyknosis, vacuolar degeneration and inflammatory cell infiltration) were observed in the model group. Compared with the model group, the pathological changes of brain tissue in the electroacupuncture group improved, the degree of neuronal injury was reduced, more normal cells were observed, the cell contour was clear, and the number of inflammatory cells decreased. (3) Contents of TNF-α, IL-6, Glu and MDA in the ischemic cortex: compared with the sham operation group, the contents of TNF-α, IL-6, Glu and MDA in the model group and the electroacupuncture group significantly increased (P<0.05). Compared with the model group, the contents of TNF-α, IL-6, Glu and MDA in the electroacupuncture group decreased significantly (P<0.05). (4) Expression level of RFK and NOX2 protein and the transcription level of RFK and NOX2 mRNA: compared with the sham operation group, expression level of RFK and NOX2 protein and the transcription level of RFK and NOX2 mRNA in the model group increased significantly after treatment (P<0.05). Compared with the model group, expression level of RFK and NOX2 protein and the transcription level of RFK and NOX2 mRNA in the electroacupuncture group decreased significantly after treatment (P<0.05).ConclusionElectroacupuncture can improve neurological impairment and limb spasm in rats with PSS, and its mechanism may be to the reduction down-regulation of Glu content in the cortex, reduction of the secretion of inflammatory cytokines TNF-α and IL-6, the inhibition of RFK and NOX2 expression, and the reduction of oxidative stress levels.